ANALISA KINERJA KEUANGAN PADA PERUSAHAAN METAL AND ALLIED PRODUCT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Juniarti Juniarti; Salamatun Asakdiyah (Jurnal Fokus Manajemen Bisnis, 2014)
The financial performance of companies known by analysing financial statements, the analysis conducted is the Current Ratio, Liquidity Ratio, Ratio of Current Assets Cash and Cash Ratio of Current Debt, Solvency Ratio of Total Debt for Equity and Debt Ratio of Assets, Ratio of Total Activity Assets Turnonver Ratio and Inventory Turnover Ratio, Profitability Ratio of Profit Margin Ratio and Return On Investment Ratio. This study used secondary data contained in the Indonesia Stock Exchange in the form of financial statement balance sheet and profit and loss of all three Metal and Allied Products Company for five years from 2005-2009. By using ratios – financial ratios above then the results is to provide ratings (ranking) on each – each company include: PT. Betonjaya Manunggal Tbk., rank (rank), the first based on the financial performance ratios liquidity ratios, solvency, activity, and profitability. PT. Lion Metal Works Tbk., rank (rank), second because one ratio is the ratio of the activity on the total asset turnover underperforming because fewer than than 1 times the velocity. PT, Jaya Pari Steel Tbk., rank (rank) third because in addition to the activity ratio, second ratio is the ratio of fluctuating liquidity and profitability ratios is not good.